2014
DOI: 10.1016/j.neuron.2014.10.022
|View full text |Cite
|
Sign up to set email alerts
|

An eIF4E1/4E-T Complex Determines the Genesis of Neurons from Precursors by Translationally Repressing a Proneurogenic Transcription Program

Abstract: Here, we have addressed the mechanisms that determine genesis of the correct numbers of neurons during development, focusing on the embryonic cortex. We identify in neural precursors a repressive complex involving eIF4E1 and its binding partner 4E-T that coordinately represses translation of proteins that determine neurogenesis. This eIF4E1/4E-T complex is present in granules with the processing body proteins Lsm1 and Rck, and disruption of this complex causes premature and enhanced neurogenesis and neural pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
118
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(124 citation statements)
references
References 30 publications
(55 reference statements)
6
118
0
Order By: Relevance
“…We have, however, shown that almost all of the nanos1 mRNA that is associated with Smaug2 in Pax6-positive precursors is also colocalized with 4E-T, which is distantly related to the Drosophila Cup. These large 4E-T-containing granules also contain Dcp1, eIF4E, Rck, and Lsm1 (shown in Yang et al, 2014) and thus resemble the P-bodies that are seen in other cells (Dostie et al, 2000;Ferraiuolo et al, 2005). Thus, P-body-like, 4E-Tcontaining granules are a major site for the Smaug2/nanos1 mRNA complex and likely for many other repressive complexes in radial precursors.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…We have, however, shown that almost all of the nanos1 mRNA that is associated with Smaug2 in Pax6-positive precursors is also colocalized with 4E-T, which is distantly related to the Drosophila Cup. These large 4E-T-containing granules also contain Dcp1, eIF4E, Rck, and Lsm1 (shown in Yang et al, 2014) and thus resemble the P-bodies that are seen in other cells (Dostie et al, 2000;Ferraiuolo et al, 2005). Thus, P-body-like, 4E-Tcontaining granules are a major site for the Smaug2/nanos1 mRNA complex and likely for many other repressive complexes in radial precursors.…”
Section: Discussionmentioning
confidence: 87%
“…In utero electroporations were performed as previously described (Gauthier et al, 2007;Yang et al, 2014). Briefly, a nuclear EGFP plasmid (pEF-EGFP) was coelectroporated with shRNA or overexpression vectors at a 1:3 ratio, or when two additional plasmids were coelectroporated, at a 1:2:2 ratio for a total final DNA concentration of 4.0 g/l.…”
Section: Methodsmentioning
confidence: 99%
“…Four of these proteins-EIF4ENIF1, REL, TCF4, and TRAF2-play important roles in the regulation of neuronspecific differentiation or apoptosis. [62][63][64][65] Two of the interactors, GOLGA2 and ZBED1, have been implicated in cell-cycle control and cell proliferation. 66,67 TRIP6 is a positive regulator of lysophosphatidic acid (LPA)-induced cell migration.…”
Section: Genetics In Medicinementioning
confidence: 99%
“…Conditional Pten deletion increases mTORC1 signaling in HSCs (Lee et al 2010), increasing 4E-BP phosphorylation (Magee et al 2012), elevating protein synthesis, and promoting HSC depletion (Yilmaz et al 2006;Signer et al 2014). It is not clear whether 4E-BPs regulate HSC function, although knockdown of 4E-BP2 (Hartman et al 2013) or eIF4E1 (Yang et al 2014) in neural progenitors increases protein synthesis and promotes premature neuronal differentiation.…”
mentioning
confidence: 99%